Analyzing the Landscape of School Effectiveness: A Literature Review - Regassa, Tolcha Eshete; Gemeda, Mitiku Bekele (Darul Yasin Al Sys, 2025)
This literature review examines the concept of school effectiveness and its measurement in educational landscapes. The study explores different perspectives on school effectiveness, including its definition, factors contributing to it, and approaches for assessing it. Key characteristics of effective schools are identified, such as a positive school culture, strong instructional leadership, clear mission statements, frequent monitoring of student progress, and high expectations for students. The review also discusses theoretical views on organizational effectiveness in schools. The findings highlight the need for further research to develop a universally accepted definition of school effectiveness and explore the interaction between internal and external factors in shaping effective schools. Generally, this literature review contributes to our understanding of how schools can promote student performance and improve educational outcomes through effective practices.